Sustainable rural development: that distinguished stranger (a review) - Bustillo García, Lissette; Martínez Dávila, Juan Pablo; Gallardo López, Felipe (Revista Científica de la Facultad de Ciencias Veterinarias)
To analyze the importance of Sustainable Rural Development (SRD), the literature was reviewed for philosophical and theoretical elements of global experiences. The final objective was to construct a conceptual and operational model of SRD which could be evaluated using interactive approximations. This proposal is based on the democratic participation of targeted communities and management of their environmet to achieve balanced and sustainable development. Environmental management thus combines the objectives of political and economic democracy with social and cultural ones through a process of economic and political descentralization. It is guided by principles of ecological organization surrounding production activities, ethnic and biological diversity in the environmet, and productive self-management of the communities. The proposed concept of SRD, being a mental abstraction and a time involved process with different socio-economic and environmental contexts, cannot be constructed as a general statement. Instead, it is likely that its design would be more useful at providing general insights for others communities.